Thermal stability of polyphenylsilsesquioxane‐modified meta‐aramid insulation paper. Issue 3 (1st June 2020) - Tang, Chao; Zheng, Wei; Wang, Lihan; Xie, Jufang
Abstract : The development of new materials for use in advanced distribution transformers is required to improve their heat resistance rating, operational safety, and reliability. The combination of polymer and nanoparticles is the preferred approach to improve the thermal stability of materials. In this study, the thermal stability of laboratory‐prepared meta‐aramid insulation paper modified with polyphenylsilsesquioxane (PPSQ) was evaluated. The results showed that the thermal stability of the modified insulation paper was superior to that of the unmodified paper. Molecular dynamics simulations were used to analyse the internal mechanism of the performance improvement achieved by modification with PPSQ. From a microscopic perspective, the addition of PPSQ provided a relatively larger structural space for the meta‐aramid fibre and increased the free volume of the entire system, which tightened the meta‐aramid fibre molecular chains, increased the density of the structure of the paper, and enhanced the mutual permeability between meta‐aramid fibre chains. Therefore, the stress can be better transmitted, the performance loss such as phase delamination was effectively prevented, and the bonding between the meta‐aramid fibres was strengthened.